PENGARUH KUALITAS PRODUK, LOKASI, DAN FASILITIAS TERHADAP MINAT BELI KONSUMEN - Coanto, Vicky Valdian; Novaria, Rachmawati; Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2018)
Surabaya is the capital of the representatives in Indonesia second largest, cities with place strict business competition. One of the ways is the culinary business began to get a bit from street vendors five to a restaurant starry five. Tavern the cowboy burger Surabaya is a place of research. The purpose of this study is to find how big the influence of the product quality, the location and facilities to consumer interest in buying.This is kind of research quantitative research. Population research is the consumers tavern the cowboy burger Surabaya. While a total 100 respondents sample by using the method the sampling method of accidental and collecting data on the use of questionnaires. Data analysis techniques used in this research was multiple linear regression analysis. The result of the research indicated that, the product quality, the location and facilities have a strong impact in together – the same against the consumer interest in buying in tavern you see, cowboys burger Surabaya. Based on a conclusion, expected tavern the cowboy burger Surabaya strategic location could pay more attention, to affect the interest of consumers low purchasing.Keywords: quality products, location, facilities, interest in buying consumers.